Fugue: A Short Story (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2019)
In this short story, composed for a beginning fiction workshop, a "young" man struggles to reconcile his past and his present, after nearly 140 years of separation from society and shunning by his own family. For additional context, listen to the author's reflection on the piece below.